FAMILY PIERIDE (LEPIDOPTERA, PIERIDAE) AND EVOLUTION OVER TIME IN FOREST GROVE SIBIU (SIBIU, ROMANIA) - Cristina STANCĂ - MOISE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2015)
Transylvania, with its geographic location, flora and fauna is a well defined region, whereby, in addition to many common elements with neighboring areas, there are also some characteristic species, which so far continue to maintain the "endemic" status. The previous decades were very important for the development of Lepidopterological research in Sibiu and Transylvania, in the postwar years. The richness of insect fauna and especially the numerous species of Lepidoptera as of its existing knowledge of this group of insects stimulated the curiosity of many researchers since the middle of the 19th century.